Implementing Lifestyle Change Interventions to Prevent Type 2 Diabetes in US Medicaid Programs: Cost Effectiveness, and Cost, Health, and Health Equity Impact - Michael Laxy; Ping Zhang; Boon Peng Ng; Hui Shao; Mohammed K. Ali; Ann Albright; Edward W. Gregg (Applied Health Economics and Health Policy, 2020)
Background: Lifestyle change interventions (LCI) for prevention of type 2 diabetes are covered by Medicare, but rarely by US Medicaid programs that constitute the largest public payer system in the USA. We estimate the long-term health and economic implications of implementing LCIs in state Medicaid programs. Methods We compared LCIs modeled after the intervention of the Diabetes Prevention Program versus routine care advice using a decision analytic simulation model and best available data from representative surveys, cohort studies, Medicaid claims data, and the published literature. Target population were non-disability-based adult Medicaid beneficiaries aged 19–64~years at high risk for type 2 diabetes (BMI ≥25~kg/m2 and HbA1c ≥~5.7% or fasting plasma glucose ≥~110~mg/dl) from eight study states (Alabama, California, Connecticut, Florida, Iowa, Illinois, New York, Oklahoma) that represent around 50% of the US Medicaid population. Incremental cost-effectiveness ratios (ICERs) measured in cost per quality-adjusted life years (QALYs) gained, and population cost and health impact were modeled from a healthcare system perspective and a narrow Medicaid perspective. Results In the eight selected study states, 1.9 million or 18% of non-disability-based adult Medicaid beneficiaries would belong to the eligible high-risk target population – 66% of them Hispanics or non-Hispanic black. In the base-case analysis, the aggregated 5- and 10-year ICERs are US226~k/QALY and US34~k/QALY; over 25~years, the intervention dominates routine care. The 5-, 10-, and 25-year probabilities that the ICERs are below US50~k (US100~k)/QALY are 6% (15%), 59% (82%) and 96% (100%). From a healthcare system perspective, initial program investments of US800 per person would be offset after 13~years and translate to US548 of savings after 25~years. With a 20% LCI uptake in eligible beneficiaries, this would translate to upfront costs of US300 million, prevent 260 thousand years of diabetes and save US205 million over a 25-year time horizon. Cost savings from a narrow Medicaid perspective would be much smaller. Minorities and low-income groups would over-proportionally benefit from LCIs in Medicaid, but the impact on population health and health equity would be marginal. Conclusions In the long-term, investments in LCIs for Medicaid beneficiaries are likely to improve health and to decrease healthcare expenditures. However, population health and health equity impact would be low and healthcare expenditure savings from a narrow Medicaid perspective would be much smaller than from a healthcare system perspective.
Keywords: 610; Pharmacoeconomics and Health Outcomes; Quality of Life Research; Health Economics; Health Administration; Public Health